Rapid Fabrication of Monolithic Carbon Aerogels Based on Resorcinol-Formaldehyde by Ambient Pressure Drying - Park, Seung-Kyu; Kim, Heon-Chang; Oh, Chang-Sup; Kim, Yong-Ha (Asian Journal of Chemistry, 2013)
New synthesis conditions to rapidly fabricate monolithic carbon aerogels based on resorcinol and formaldehyde were developed using ambient pressure drying. The resorcinol-formaldehyde aerogel network synthesized under strong basic conditions not only dramatically reduced the gelation time but also exhibited better particle connectivity. This also allowed for the rapid drying of the wet-gels and subsequent carbonization in an inert atmosphere to yield carbon aerogels. Monolithic carbon aerogels possessing both microporous and macroporous characteristics were synthesized. It was shown that the microstructure of the carbon aerogels was comprised of spherical particles that could be tailored by control of sol-gel preparation parameters, such as volume ratios of formaldehyde, deionized water and ammonium hydroxide with the resorcinol. The synthesized carbon aerogels had a tapping density as low as 0.11 g/cm3 and a specific surface area as high as 551 m2/g.